Lectin-binding pattern in ovarian structures of rats with experimental polycystic ovaries - Barbeito, Claudio Gustavo (2013)
Contents: Numerous experimental models in different species have been developed for the study of polycystic ovarian syndrome. In this study, we used a model of induction of polycystic ovaries (PO) in rats by exposure to constant light to study the distribution and variations of glycosylated residues present in the different ovarian structures. Seven biotinylated lectins were used (Con-A, WGA, DBA, SBA, PNA, RCA and UEA-I) on tissue sections, and detection was performed using the streptavidin/peroxidase method. In tissue sections was observed an increase in affinity for Con-A in the granulosa and theca interna of growing follicles and cysts in animals with PO in relation to the control group. Follicular cysts showed higher affinity for WGA and RCA-I which growing follicles in the same group, and there was a decrease in affinity for PNA in the cysts in relation to the growth of follicles in both groups. Atretic follicles in both groups showed greater labelling with lectins PNA, SBA and RCA-I in relation to healthy follicles. It could also be noted that the zona pellucida of cystic follicles lost the affinity for the lectin Con-A. There was no staining on follicles in any category with the lectins DBA and UEA-I, although it was staining in the corpus luteum (control group) and in the mesothelium and interstitial glands of both groups with DBA. These observations probably reflect changes in the glycosaminoglycans present in the different ovarian compartments or in the glycosylation of cellular components essential for proper follicular dynamics.